AB 73. Pulmonary hyalinizing granuloma: case report - Papaemmanouil, Stiliani (Pioneer Bioscience Publishing Company, 2012)
BACKGROUND: Pulmonary hyalinizing granuloma is an unusual condition, characterized by fibrosing nodules, consisting of the either unilateral or bilateral central whorled deposits of lamellar collagen hyaline. Although the etiology is uncertain there are evidences that suggest an autoimmune origin. Clinically and with imaging techniques it may be minic primary or metastatic carcinoma or nodular amyloidosis. PATIENTS AND METHODS: We report case of 74 years old woman who admitted in our hospital with cough, dyspnea and chest pain. A CT scan of the chest revealed a mass located in the middle lobe of the right lung. The patient underwent thoracotomy for surgical excision of the mass macroscopic examination of the excised lobe revealed a well-circumscribed firm, grayish-white mass, measuring 3.1 cm × 2 cm × 1.3 cm. The sections were examined with H+E, PAS, and Congo-Red and followed by immunohistochemical study for Amyloid A and P, CD138, κ and λ light chains. RESULTS: The microscopic examination with H+E showed that the lung parenchyma presented extensive hyaline fibrosis PAS positive, areas of calcification and foci of bone metaplasia, accompanied by an inflammatory reaction. Congo-Red stain was positive but screening for birefringent material under polarized light was negative. Amyloid A and P were negative. The plasma calls were positive for CD138, κ and λ light chains. These histological findings were consistent with diagnosis of pulmonary hyalinizing granuloma. CONCLUSIONS: The pulmonary hyalinizing granuloma should be considered in the differential diagnosis of pulmonary nodules or masses, even when they are cavitary or contain calcifications.